Conflict, negotiations and natural resource management : a legal pluralism perspective from India - Bavinck, Maarten, 1954-; Jyotishi, Amalendu (Milton Park : Routledge, 2014)
'Conflicts over natural resources abound in India, where much of the population is dependent on these resources for their livelihoods. Issues of governance and management are further complicated by the competing claims of parallel legal systems, including state, customary, religious, project and local laws. Whereas much has been written about property rights with a focus on static definitions, this unique collection looks at the legal anthropological perspective, exploring how the coexistence and interaction between multiple legal orders provide bases for claiming property rights. It examines how hybrid legal institutions have developed over time in India and how these impact on justice issues in the governance and distribution of natural resources. The book brings together original case studies that offer fresh perspectives on the governance of forests, water, fisheries and agricultural land in a diverse range of social and spatial contexts. This brand new research provides a timely and persuasive overview of the fundamental role of parallel legal systems in shaping how people manage natural resources. It will be of interest to scholars and practitioners of environmental law, property law, environmental politics, anthropology, sociology and geography.'--
'This collection brings a diverse range of approaches to the question of pluralism, property and natural resource management in South East Asia. This significant contribution to the rapidly growing body of literature exploring indigenous people, legal pluralism, land rights and environmentalism is a timely and persuasive overview of the fundamental role of property rights in shaping how people manage natural resources'--
Introduction : The Legal Pluralism Perspective / Maarten Bavinck and Amalendu Jyotishi -- Law-breakers and Law-makers : Critical Legal Pluralism, Normative Subjects and Ecological Regimes in India / D. Parthasarathy -- The Godavarman Judgment : Erasing the Plurality of Land Use in Gudalur, Nilgiris / Ajit Menon -- Unearthing the Roots of Statutory Forest Law : Iron Smelting and the State in Pre- and Early-Colonial India / Sashi Sivramkrishna and Amalendu Jyotishi -- Land, Law and Resistance : Legal Pluralism and Tribal Conflicts over Land Alienation in Odisha / Satyapriya Rout -- Community Rights and Statutory Laws : Politics of Forest in Uttarakhand, Himalayas / Pampa Mukherjee -- Handling fishery conflicts in the context of legal pluralism : a case-study analysis of street-level bureaucracy in Tamil Nadu, India / Maarten Bavinck -- A political ecology of legal plural disconnection in the marine fishery of Junagadh District, Gujarat, India / Derek Johnson -- Institutional Pluralism, Multilevel Arrangements and Polycentricism : The Case of Chilika Lagoon, India / Prateep Kumar Nayak -- Legal pluralism and the governability of fisheries and coastal systems in the world : a conceptual enquiry / Svein Jentoft.
Includes bibliographical references and index.
Keywords: Legal polycentricity -- India; Environmental law -- India; Right of property -- India; Natural resources -- Law and legislation -- India; Natural resources -- Government policy -- India